Intertemporal extraction of mineral resources under variable rate taxes - CONRAD, Robert F. (Institutional Knowledge at Singapore Management University, 1984)
Variable-rate taxes are being applied with increasing frequency in the US and other countries. However, their effects typically go beyond those that have motivated their use. The formulation of mineral tax policy should take into account the complete list of consequences.-from Authors